2017
DOI: 10.1038/s41598-017-00277-7
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Solution Processed Organic Field Effect Transistors with Novel Diketopyrrolopyrrole-Containing Small Molecules

Abstract: The donor-acceptor (D-A)-type diketopyrrolopyrrole (DPP)-based small molecules (LGC-D117 and LGC-D118) were synthesized and used as the active layer of solution-processable organic field-effect transistors (OFETs). Both LGC-D117 and LGC-D118 contain silaindacenodithiophene as electron-donor units with DPP as an electron-accepting linker, and octylrhodanine as the electron-accepting end group. The molecules were functionalized with different side chains to study their effects on OFET characteristics. LGC-D117 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…7,8 Consequently, great efforts in materials design have boosted the OFET mobility values achievable from both semiconducting polymers and small molecules up to near 1 cm 2 V -1 s -1 . [7][8][9][10][11][12][13][14][15] Furthermore, several recent papers have reported that mobility values surpassing 10 cm 2 V -1 s -1 can be obtained. 16,17 In spite of the numerous milestone achievements for OFET devices in the last 10 years, it remains a challenge to develop new molecular systems suitable for transistor applications because many synthesized materials did not work or showed very low mobility in OFET devices, and most high mobility OFET materials were achieved through slight modification of the existing semiconductors with high performance mainly by changing one of the alternative building blocks in polymeric materials or replacing the flexible side chains of workable polymers or small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Consequently, great efforts in materials design have boosted the OFET mobility values achievable from both semiconducting polymers and small molecules up to near 1 cm 2 V -1 s -1 . [7][8][9][10][11][12][13][14][15] Furthermore, several recent papers have reported that mobility values surpassing 10 cm 2 V -1 s -1 can be obtained. 16,17 In spite of the numerous milestone achievements for OFET devices in the last 10 years, it remains a challenge to develop new molecular systems suitable for transistor applications because many synthesized materials did not work or showed very low mobility in OFET devices, and most high mobility OFET materials were achieved through slight modification of the existing semiconductors with high performance mainly by changing one of the alternative building blocks in polymeric materials or replacing the flexible side chains of workable polymers or small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Organic conjugated materials offer several benefits in both OFET and OPV devices, including flexibility in synthesis, solution-processability and tunable charge transport and optical properties via molecular structure engineering. [14][15][16][17][18][19][20][21][22][23] Among various conjugated building blocks for high performance organic semiconductors, diketopyrrolopyrrole (DPP) is one of the most promising moieties and favourable choice of many synthetic chemists. 24 For instance, high carrier mobility values of over 10 cm 2 V -1 s -1 and high power conversion efficiencies (PCE) of up to 9.40% have been achieved with DPPbased materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the rigid part consisting of bis‐DPP and thiophenes in polymer induces low solubility. Thus, previous studies reported that it is necessary for several DPP and thiophenes‐based D–A polymers to incorporate relatively long and bulky side chains to provide sufficient solubility in common organic solvents for processing . However, these types of long and bulky side chains hinder strong molecular packing and long‐range ordering of conjugated polymer backbone for efficient intermolecular charge transport.…”
Section: Resultsmentioning
confidence: 99%